(untitled) (Sebha University Conference Proceedings, 2025)
The silicon insulated gate bipolar devices (silicon IGBTs) are typically employed in construction of Traditional High frequency converter cabinet (THFCC), which are used to integrate utility grid with aircraft ground stations. Due to the physical limitations of silicon switches, the efficiency of THFCC can be enhanced by substituting silicon carbide IGBT for the existing silicon IGBTs devices. The main goal of this study was to demonstrate that the use of silicon carbide IGBTs in THFCC might result in increased efficiency because of their higher switching speeds and power density. This was demonstrated through actual experimental investigations. This work investigated two experimental configurations, the single pulse test (SPT), which uses silicon IGBT and silicon carbide IGBT. The THFCC with only silicon IGBT is implemented and tested to investigate the features of the silicon IGBT. The potential gain in efficiency if silicon carbide IGBTs are used in THFCC in the next study. The test findings yielded a number of interesting observations. At a switching frequency of 20 kilohertz, THFCC with silicon carbide IGBTs efficiency of 85% is achievable. Investigations were conducted into the on/off processes. Experimental silicon IGBT efficiency in SPT was 77%, whereas silicon carbide IGBTs efficiency was 95%. Furthermore, an examination of further aircraft ground stations has been conducted, focusing on semiconductor devices, field applications, and output filters.